Effects of sedation and salbutamol administration on hyperpnoea and tidal breathing spirometry in healthy horses. (April 2017) - Raidal, S.L.; Burnheim, K.; Evans, D.; Hughes, K.J.
Highlights: Xylazine had greater effect on respiratory function than acetylpromazine. Effects of sedation were attenuated during rebreathing. Inspiratory relative flow-time indices were unaffected by sedation. Salbutamol increased peak inspiratory airflow in healthy horses. Abstract: Sedation is often required to perform pulmonary function testing (PFT) in horses, but drug effects may influence respiratory function. The current study was designed to characterise the effects of sedation and bronchodilator administration on absolute and relative indices of pulmonary function during eupnoeic respiration and carbon dioxide-induced hyperpnoea (rebreathing) in healthy horses using a pneumotachographic spirometry system. Sedation with acetylpromazine (ACP), xylazine, or both drugs in combination was associated with significant reductions in respiratory frequency, minute ventilation and peak airflows during eupnoeic respiration. Peak expiratory airflow occurred later in the respiratory cycle than was observed in untreated horses, and expiratory relative flow-time indices were also affected during eupnoeic respiration. Rebreathing attenuated the effects of sedation on indices of pulmonary function, suggesting that future studies should consider the use of induced hyperpnoea as part of the spirometry protocol. Based on the finding that all sedative agents had some effect on eupnoeic respiration, albeit least pronounced with ACP, the latter drug should be considered for sedation of horses undergoing PFT. Salbutamol increased peak inspiratory flow during eupnoeic respiration in healthy horses.